2019
DOI: 10.1177/1049732319869909
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Paradoxes: A Systematic Review of Qualitative Family Perspectives on Living With Congenital Heart Defects

Abstract: There have been substantial advances in the diagnostics and treatment of congenital heart defects (CHDs) in recent decades, and this has improved survival significantly. Consequently, there is a growing interest in how CHDs affect the daily lives of children and youth. We examine life with CHDs as a particular kind of living from the perspectives of both children and youth with CHDs and their families through a systematic review of existing qualitative research. Based on a meta-ethnographic analysis of 20 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
(182 reference statements)
1
3
0
Order By: Relevance
“…However, previous studies have revealed that family members may avoid social relationships and isolate themselves to hide their family's illness (Park & Park, 2014), which places a burden on the family members and the family as a whole. Our findings are consistent with previous studies that suggest that living with CHD contributes to others perceiving the family in a negative and judgemental way and can bring stigma and discrimination to the family (Elissa et al., 2018; Ni et al., 2019; Svensson et al., 2020). In Chinese culture, people follow the preordained Confucian route to self‐cultivation more out of fear of losing face than in an attempt to gain face, and being publicly insulted or humiliated will cause one to lose face.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, previous studies have revealed that family members may avoid social relationships and isolate themselves to hide their family's illness (Park & Park, 2014), which places a burden on the family members and the family as a whole. Our findings are consistent with previous studies that suggest that living with CHD contributes to others perceiving the family in a negative and judgemental way and can bring stigma and discrimination to the family (Elissa et al., 2018; Ni et al., 2019; Svensson et al., 2020). In Chinese culture, people follow the preordained Confucian route to self‐cultivation more out of fear of losing face than in an attempt to gain face, and being publicly insulted or humiliated will cause one to lose face.…”
Section: Discussionsupporting
confidence: 93%
“…For this reason, families of children with CHD may consider the disease to be a family stigma and prefer to hide the disease to protect the family's reputation and not risk jeopardising the social standing of the family, which places a burden on the family members and the family as a whole (Elissa et al., 2018; Svensson et al., 2020). With this in mind, policymakers and healthcare providers should act to eliminate stigma by providing appropriate educational programs that focus on the symptoms, causes, and effects of CHD (Elissa et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…From the above results, it can be seen that the CHD children’s family stressor scale is an effective and reliable tool for evaluating the stressors of CHD children’s families. Numerous studies have shown that families of children with CHD suffer from physical, psychological and economic torment during the long process from diagnosis to surgery, and they face stressors from different aspects ( 49 ). How to better manage stress is one of the important issues faced by families of children with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…2 This might have an impact on children's everyday life and in research nowadays involving children with CHD, the focus has changed from survival to how these children experience their everyday life. 5 Earlier studies have shown that they experience physical activities limitation 6,7 and feelings of isolation, 8 but no study has yet studied how children with right ventricle outflow tract anomalies experience their everyday life. To be able to provide support, studies are needed to explore how these children experience the period from assessment to decision, as well as the months thereafter.…”
mentioning
confidence: 99%